Perancangan dan Implementasi Sistem Inventory Berbasis Web pada Usaha Ritel Bangunan TB Lancar Maron - Desidarius Eduardo Djee Belly; Verdi Yasin; Anton Zulkarnain Sianipar (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
This study aims to design and implement a web-based inventory information system at TB Lancar Maron to replace the previously manual system used for managing stock records. The previous system faced several issues, including data entry errors, delayed reporting, and stock inconsistencies, which hindered efficiency and effectiveness in inventory management. The system development process followed the Scrum approach within the Agile methodology, starting from sprint planning, user requirement gathering, system design, to implementation and evaluation stages. The technologies employed included Laravel framework for backend development, MySQL for database management, and a responsive web interface for accessibility. The implementation results show that the system is capable of recording incoming and outgoing goods in real time, generating automated reports, and allowing the store owner to monitor stock levels from any internet-connected device. System performance was evaluated through direct testing by administrators and staff, and the outcomes indicated improved work efficiency, stock data accuracy, and ease of reporting. Furthermore, the new system successfully minimized common errors that occurred with the manual method. With this new solution, TB Lancar Maron benefits from a professional and integrated digital inventory management system. This study is expected to serve as a reference for the application of inventory information systems in small and medium-sized retail businesses.